Characterisation of microfibrils cellulose isolated from oil palm frond using high-intensity ultrasonication. Issue 1 (August 2021) - Yashim, M M; Mohammad, M; Asim, N; Fudholi, A; Abd Kadir, N H
Abstract: This study highlighted the utilization of agricultural byproducts as an alternative fiber resource to be used as one of the materials for reinforcement biocomposite. Cellulose was extracted from oil palm frond using the alkaline treatment and successfully isolated into microfibril via the combination of carboxymethylation pre-treatment ultrasonication to get highly crystalline and good thermal stable microfibers. 4% NaOH was used during alkaline treatment and followed by oxidative bleaching with 30% H2O2. Once the extracted cellulose is chemically pre-treated with monochloroacetic acid, it was subjected to 30 minutes ultrasonication treatment to reduce its size. The detailed comparative analysis using SEM, FTIR and TGA was conducted in this work revealed some breakages of intramolecular hydrogen bonds and glycosidic bonds that occurred during the alkaline and bleaching treatment of oil palm biomass. The SEM images showed significant morphology of rigid, organized and highly ordered cellulose fibrils changed into aggregated fibril bundles of microfibrils after ultrasonication. The results from the infrared spectrums revealed that the mild alkaline treatments and oxidative bleaching were able to remove a large fraction of lignin and hemicelluloses to leave a clean cellulose sample. The isolated microfibrils cellulose exhibit good thermal stability as almost 50% of its initial mass remains at a temperature of 300 °C. These findings demonstrate that oil palm fronds can be utilized for biocomposite reinforcement applications.